How do you evaluate the integral of #int t^2*e^(-5*t) dt#?

Answer 1

#-t^2/5e^(-5t)-(2t)/25e^(-5t)-2/125e^(-5t)+C#

We will use integration by parts. This takes the form #intudv=uv-intvdu#. When we choose values for #u# and #dv#, we want our value of #u# to become simpler as we differentiate it.
So, let #u=t^2# and #dv=e^(-5t)dt#. So, #du=2tdt# and #v=inte^(-5t)dt=-1/5e^(-5t)#.

So:

#intt^2e^(-5t)dt=uv-intvdu#
#color(white)(intt^2e^(-5t)dt)=t^2(-1/5e^(-5t))-int(-1/5e^(-5t))(2tdt)#
#color(white)(intt^2e^(-5t)dt)=-t^2/5e^(-5t)+int2/5te^(-5t)dt#
Again, we need integration by parts. Let #u=2/5t# so #du=2/5dt#. Again let #dv=e^(-5t)dt# so again #v=-1/5e^(-5t)#.
#color(white)(intt^2e^(-5t)dt)=-t^2/5e^(-5t)+(uv-intvdu)#
#color(white)(intt^2e^(-5t)dt)=-t^2/5e^(-5t)+2/5t(-1/5e^(-5t))-int(-1/5e^(-5t))(2/5dt)#
#color(white)(intt^2e^(-5t)dt)=-t^2/5e^(-5t)-(2t)/25e^(-5t)+int2/25e^(-5t)dt#
Using the integral from before, #inte^(-5t)dt=-1/5e^(-5t)#:
#color(white)(intt^2e^(-5t)dt)=-t^2/5e^(-5t)-(2t)/25e^(-5t)-2/125e^(-5t)+C#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To evaluate the integral of ∫ t^2 * e^(-5t) dt, you can use integration by parts. The formula for integration by parts is:

∫ u dv = u * v - ∫ v du

In this case, let u = t^2 and dv = e^(-5t) dt. Then, differentiate u to get du and integrate dv to get v:

du = 2t dt v = (-1/5) * e^(-5t)

Now, apply the integration by parts formula:

∫ t^2 * e^(-5t) dt = t^2 * (-1/5) * e^(-5t) - ∫ (-1/5) * e^(-5t) * 2t dt

= (-t^2/5) * e^(-5t) + (2/5) * ∫ t * e^(-5t) dt

Now, you can use integration by parts again for the remaining integral:

Let u = t and dv = e^(-5t) dt. Then, du = dt and v = (-1/5) * e^(-5t).

Apply the integration by parts formula:

∫ t * e^(-5t) dt = t * (-1/5) * e^(-5t) - ∫ (-1/5) * e^(-5t) * dt

= (-t/5) * e^(-5t) + (1/5) * ∫ e^(-5t) dt

= (-t/5) * e^(-5t) - (1/25) * e^(-5t) + C

Substitute this back into the previous expression:

(-t^2/5) * e^(-5t) + (2/5) * [(-t/5) * e^(-5t) - (1/25) * e^(-5t)] + C

= (-t^2/5) * e^(-5t) - (2/25) * t * e^(-5t) + (2/125) * e^(-5t) + C

So, the integral of ∫ t^2 * e^(-5t) dt is (-t^2/5) * e^(-5t) - (2/25) * t * e^(-5t) + (2/125) * e^(-5t) + C, where C is the constant of integration.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7